The color of the third degree: racism, police torture, and civil rights in the American South, 1930-1955 - Niedermeier, Silvan (The University of North Carolina Press, 2019)
Police torture and "legal lynchings" in the American South -- Torture and African American courtroom testimony -- The NAACP campaign against "forced confessions" -- Selective public outrage: the Quintar South case -- The investigations by the federal government.